If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -1.5) + -2x = 17 Reorder the terms: 3(-1.5 + 4x) + -2x = 17 (-1.5 * 3 + 4x * 3) + -2x = 17 (-4.5 + 12x) + -2x = 17 Combine like terms: 12x + -2x = 10x -4.5 + 10x = 17 Solving -4.5 + 10x = 17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4.5' to each side of the equation. -4.5 + 4.5 + 10x = 17 + 4.5 Combine like terms: -4.5 + 4.5 = 0.0 0.0 + 10x = 17 + 4.5 10x = 17 + 4.5 Combine like terms: 17 + 4.5 = 21.5 10x = 21.5 Divide each side by '10'. x = 2.15 Simplifying x = 2.15
| 8*(x-2)=32 | | 9+4*x=29 | | 315=7(6m+3) | | 12-3*x=3 | | -2x-4=32 | | 7x-17=6x+7 | | (X+6)+x+2x=35 | | .333x-4=2 | | 2*(y^2)-x^2=0 | | -2(12)+12y=47 | | -16x+7=-41 | | -2(-12)+12y=47 | | 2(x+7)+3(x-5)= | | .09X+X=100 | | -48-12x=8 | | -2(-2)+12y=47 | | 7n-3n=19 | | 4i^5= | | -2c(-c-12)=-2c-12 | | -5(7x-9)=-35x+45 | | -8x-2=-x+3 | | 368=-7x+8(-5x-1) | | 5i^10= | | 15cos^2+(4cos)-3=0 | | 2y+4=-2x+6 | | 4x^2-60x-70=0 | | 6y=18x+36 | | (2+3i)(5-3i)(-7+I)= | | 6+4=-5 | | 6x-4=-50 | | (4+6i)-(5+3i)= | | 4x+4=29 |